Validation of the Korean version of the 39-Item Parkinson's Disease Questionnaire (PDQ-39) - Hye-Ja Park, PhD; Kyeong-Yae Sohng, PhD; Sehyun Kim, PhD (Elsevier, 2014)
Purpose: To evaluate the reliability and validity of the Korean version of the 39-item Parkinson's disease questionnaire (PDQ-39). Methods: Cross-cultural adaptation was performed according to the international guidelines: forward and backward translation, focus group meeting, and a field test. With Korean consensus translation produced, validation was assessed by evaluating reliability and validity. Ninety-three outpatients with Parkinson's disease (PD) and 89 healthy aged controls were recruited. Internal consistency reliability was assessed by Cronbach's alpha. Validity was assessed by Spearman correlation analysis, t test, factor analysis, and analysis of variance with Duncan's multiple range tests. Results: In the PD group, mean age was 65.13 ± 9.84 years, and mean duration of PD was 42.41 ± 37.01 months. Ceiling and floor effects ranged 1.1%-2.2% and 1.1%-15.1%, respectively. Cronbach's alpha of eight dimensions ranged from .70 to .97. All dimensions were correlated with each other, except for the stigma dimension. PD patients had significantly lower quality of life than healthy aged controls did, except for the bodily discomfort dimension. Eight dimensions of Korean PDQ-39 loaded on one factor. PD patients with a Modified Hoehn and Yarh Staging score of 4 had the worst quality of life. The relationships among the eight dimensions of Koran PDQ-39 and the Modified Hoehn and Yarh Staging is fair to good, except for the stigma and social support dimension. Conclusion: The Korean PDQ-39 was proved to be reliable and valid. Our results suggest that Korean PDQ-39 could be used in clinical research to assess and evaluate the disease process and its impacts on health-related quality of life in Korean PD patients.